A Feedforward Mechanism for Epileptogenesis Regulated by Lactate Dehydrogenase A. (1st September 2019) - Altshuler, Marcelle; Ksendzovsky, Alexander; Bachani, Muznbanu; Walbridge, Stuart; Inati, Sara; Fayed, Islam; Heiss, John D; Kapur, Jaideep; Zaghloul, Kareem A
Abstract: INTRODUCTION: Despite the ketogenic diet's successful use since the 1920s, epilepsy as a disease of energy metabolism is a novel concept. We previously established that seizures deplete neuronal energy stores and reprogram neurons from aerobic to glycolytic metabolic phenotype, marked by upregulation of lactate dehydrogenase A (LDHA). LDHA has recently been shown to play a role in neuronal membrane depolarization and epileptogenesis. We show here that LDHA upregulation through HIF1a may lead to seizure formation. METHODS: Resected tissue from 11 epileptic patients were probed for LDHA expression. To study the electrophysiological consequences of LDHA, we used a mixed rat cortical cell culture model on a microelectrode array (MEA). Furthermore, we developed a novel murine model of chronic focal cortical epilepsy to establish HIF1a's role in mediating LDHA expression and seizure formation. Finally, we used a lentivirus vector to directly upregulate LDHA in neurons cultured on an MEA to measure neuronal bursting. RESULTS: We found LDHA increased significantly in epileptic tissue versus nonepileptic tissue. Induction of seizure activity in cultured neurons with low magnesium resulted in increased LDHA and subsequently increased baseline bursting over 10 d. Inhibition of LDHA activity with stiripentol and isosafrole decreased the overall burst frequency. Cells that were induced to upregulate LDHA via DMOG, an upstream HIF1a potentiator, showed a significant increase in baseline bursting activity. Furthermore, placement of cobalt, a HIF1a stabilizer, into the frontal cortex of mice caused chronic seizures emanating from perilesion cortex which showed increased LDHA. Finally, direct LDHA upregulation resulted in increased bursting activity confirming that LDHA may lead to seizure formation. CONCLUSION: Overall, our data show that LDHA, regulated by HIF1a, can contribute to seizure development. These data suggest a novel molecular mechanism for the pathogenesis of epilepsy where seizures cause LDHA upregulation which then further drives seizures, leading to a cycle of epileptogenesis.